Polystyrene Microsphere-Based Immunochromatographic Assay for Detection of Aflatoxin B1 in Maize - Jin Wang; Xiangmei Li; Xing Shen; Ang Zhang; Jinxiu Liu; Hongtao Lei (Biosensors, 2021)
Aflatoxin B1 (AFB1), a mycotoxin, is hepatotoxic, carcinogenic, and nephrotoxic in humans and animals, and contaminate a wide range of maize. In this study, an immunochromatographic assay (ICA) based on polystyrene microspheres (PMs) was developed for sensitive and quantitative detection of AFB1 in maize. The amounts of PMs, the condition for activating carboxyl groups of PMs, the amount of monoclonal antibody (mAb), and the volume of the immune probe were optimized to enhance the performance PMs-ICA for point-of-care testing of AFB1 in maize. The PMs-ICA showed the cut-off value of 1 ng/mL in phosphate buffer (PB) and 6 µg/kg in maize samples, respectively. The quantitative limit of detection (qLOD) was 0.27 and 1.43 µg/kg in PB and maize samples, respectively. The accuracy and precision of the PMs-ICA were evaluated by analysis of spiked maize samples with recoveries of 96.0% to 107.6% with coefficients of variation below 10%. In addition, the reliability of PMs-ICA was confirmed by the liquid chromatography-tandem mass spectrometry method. The results indicated that the PMs-ICA could be used as a sensitive, simple, rapid point-of-care testing of AFB1 in maize.